Religion for Slaves Difficulties and Methods - Perkins, Haven P. (1941)
I confine myself largely to the period between 1830 and 1850 and to the movement for additional religious instruction of slaves which flourished during those years, though it did not end in 1850. The sources on which the analysis is based represent conditions in South Carolina and Georgia, with a moderate sampling of Alabama and Mississippi, and not a great deal for the border states.
Keywords: Reformierte Kirchen; USA/United States of America/Vereinigte Staaten von Amerika; Jahrhundert, 19; Sklaverei; Reformed Churches; USA/United States of America; century, 19th; Slavery